Characterisation and energy assessment of fats, oils and greases (FOG) waste at catchment level. (15th February 2020) - Collin, Thomas; Cunningham, Rachel; Jefferson, Bruce; Villa, Raffaella
Graphical abstract: Highlights: 240 TWh.year −1 could be generated from food outlets' FOG in the London area. FOG collected further away from source were richer in water and other contaminants. FOG demonstrated high biomethane potentials. Lipids accounted for most of the organic in FOG. A shift from unsaturated to saturated fats was noticed from source to end point. Abstract: Several of the waste materials that have a negative impact on the sewer system are produced by fats, oils and greases (FOG) discharged from commercial and domestic kitchens. These materials accumulate at different points in the sewer catchment, from kitchens to pumping stations, sewers and sewage treatment works (STWs), and comprise oily wastewater, floating agglomerates and hard deposits. Despite their detrimental effects, these waste materials have a high calorific content and are an ideal feedstock for energy recovery processes. So far, the overall volume of each type of waste and their physical-chemical properties in relation to their collection point are unknown. However, from a management point of view, knowledge on each feedstock quality and volumes is necessary to develop an economic viable solution for their collection and for energy recovery purposes. In this study, FOG wastes collected from households, food service establishments (FSEs), sewage pumping stations, sewers and STWs, were compared to sewage sludge in terms of organic contents and energy potentials. As expected, FOG recovered at source (households and FSEs) were 'cleaner' and had a higher energy content. Once mixed with wastewater the materials changed in composition and lost some of their energy per unit mass. Our results showed that around 94, 730 tonnes.year −1 of these materials could be recovered from the Thames Water Utilities' catchment, one of the most populated in the UK. These materials could produce up to 222 GWh.year −1 as biogas, close to double of what is produced with sewage sludge digestion and around 19% of the company energy needs. Finally, even with over six million households in the catchment, the results showed that most of the FOG waste was produced by FSEs (over 48, 000 premises) with an estimated average of 79, 810 tonnes.year −1 compared to 14, 920 tonnes.year −1 from private households. This is an important outcome as recovery from FSEs will be cheaper and easier if the company decides to implement a collection system for energy recovery.